DESIGN OF WIRELESS SENSOR NETWORK SYSTEM FOR LAND FIRE DETECTION - Apriyaldi Lukman; Suhirman Suhirman; Wibawa Wibawa (Jurnal Dinamika Informatika, 2020)
Wireless Sensor Network is one of the new technology for monitoring a system that is widespread enough and does not allow data communication through the usual cable network. By utilizing the sensors MQ-2 officers can monitor the Android application already installed on Android phones and in case of land fires, the officer is more efficient to perform extinguishing actions so that the fire is not widespread. Then the system can produce land fire information. The research is aimed at knowing the information of land fires anywhere, using the Waterfall method. The software used is Android Studio, Arduino sketch, Firebase as the database server. The result of the research is a system that makes it easier for firefighters to directly locate.